RONGGENG DUKUH PARUK DAN PEREMPUAN KEMBANG JEPUN (KAJIAN SASTRA BANDING) - Inung Setyami (Jurnal Ilmu Budaya, 2022)
This study aims to discribe the form of subordination experienced by geisha in the novel Perempuan Kembang Jepun by Lan Fang and Ronggeng in the novel Ronggeng Dukuh Paruk by Ahmad Tohari. The data source of this research used two novels, namely the novel Perempauan Kembang Jepun (PKJ) by Lan Fang and the novel Ronggeng Dukuh Paruk (RDP) by Ahmad Tohari. The results showed that 1) novel PKJ by Lan Fang and novel RDP by Ahmad Tohar, the central character is a woman who works as a dancer. Ronggeng dancers are included in RDP, while geisha are inclued in PKJ; 2) Both novels present male characters related to the geisha and ronggeng professions; 3) There are similarities in ideas, namely women in both PKJ and RDP novels experience subordination to male power that has been socially constructed; 4) Biologically, dancers in PKL and RDP have the idea of eliminating the absolute nature of women (pregnancy, giving birth); 4) There are absolute requirements for prospective dancers, namely mizuage (virginity auction) for geisha candidates and "bukak klambu" (virginity contest) for ronggeng candidates.